Nationwide study of in-hospital maternal mortality in Ecuador, 2015-2022 - German Josuet Lapo-Talledo (Pan American Health Organization, 2024)
Objective. This study aimed to analyze estimates of in-hospital delivery-related maternal mortality and sociodemographic factors influencing this mortality in Ecuador during 2015 to 2022. Methods. Data from publicly accessible registries from the Ecuadorian National Institute of Statistics and Censuses were analyzed. Maternal mortality ratios (MMRs) were calculated, and bivariate and multivariate logistic regression models were used to obtain unadjusted and adjusted odds ratios. Results. There was an increase in in-hospital delivery-related maternal deaths in Ecuador from 2015 to 2022: MMRs increased from 3.70 maternal deaths/100 000 live births in 2015 to 32.22 in 2020 and 18.94 in 2022. Manabí province had the highest rate, at 84.85 maternal deaths/100 000 live births between 2015 and 2022. Women from ethnic minorities had a higher probability of in-hospital delivery-related mortality, with an adjusted odds ratio (AOR) of 9.59 (95% confidence interval [95% CI]: 6.98 to 13.18). More maternal deaths were also observed in private health care facilities (AOR: 1.99, 95% CI: 1.4 to 2.84). Conclusions. Efforts to reduce maternal mortality have stagnated in recent years. During the COVID-19 pandemic in 2020, an increase in maternal deaths in hospital settings was observed in Ecuador. Although the pandemic might have contributed to the stagnation of maternal mortality estimates, socioeconomic, demographic and clinical factors play key roles in the complexity of trends in maternal mortality. The results from this study emphasize the importance of addressing not only the medical aspects of care but also the social determinants of health and disparities in the health care system.